Predictive factors for the surgical treatment of necrotizing enterocolitis in preterm infants: a single-center retrospective study - Yusheng Liu; Lingyan Qiao; Xiongwei Wu; Zhong Jiang; Xiwei Hao (BMC, 2022)
Abstract Background Necrotizing enterocolitis (NEC) is a gastrointestinal disease that tends to occur in premature infants. Some features may be associated with an increased probability that preterm infants with NEC will require surgical treatment. This study aimed to identify the factors that increased the probability of surgical treatment in infants with NEC. Methods We retrospectively analyzed the data of premature infants with NEC who were hospitalized at The Affiliated Hospital of Qingdao University from April 2011 to April 2021. According to the treatments received, these patients were divided into medical NEC group and surgical NEC group. The perinatal characteristics, clinical manifestations, and laboratory values before the onset of NEC were subjected to univariate and multivariate analyses. Results A total of 623 preterm infants with NEC (> Bell's stage I) were included in this study, including 350 (56%) who received surgical treatment and 273 (44%) who received conservative medical treatment. Multivariate analysis showed that lower gestational age (P = 0.001, odds ratio (OR) (95% CI) = 0.91[0.86-0.96]), early occurrence of NEC (P = 0.003, OR (95% CI) = 0.86 [0.77-0.95]), hemodynamically significant patent ductus arteriosus (P = 0.003, OR (95% CI) = 7.50 [2.03-28.47]), and low serum bicarbonate (P = 0.043, OR (95% CI) = 0.863 [0.749-0.995]) were associated with an increased probability of surgical treatment in preterm infants with NEC. Conclusions Our findings were applied to identify potential predictors for surgical treatment in preterm infants with NEC, which may facilitate early decisive management.